(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Agriculture in India has become the site of marginalization of indigenous knowledge systems on farming, cropping, and cultivation to modern scientific knowledge on agricultural practices and irrigation. Modern scientific knowledge is seen as the premier of development and economic efficacy. The interaction of the existing knowledge system with modernity and scientific knowledge in India has resulted in hierarchies in agricultural production and emergence of cash crops. The path of development followed by India after colonialism to battle poverty and hunger was to match the western modern-scientific cannons. This kind of economic planning and technological advancement also resulted in the green revolution and High yielding variety of seeds (Hyv) of rice and wheat. The production of rice and wheat boomed since then and millets in India became “Coarse grains” with constant declining production over the last six decades. The prevalent crisis of malnutrition today has established the fact that India‟s road to development was unsustainable. It actively marginalized the production of millet in India which were the nutritional supplement in the diets of the poor, especially tribals and farmers of arid regions. The traditional production of millets by the tribals and the farmers maintained the balance between ecology and consumption. But modern scientific practices of agriculture and the use of chemical fertilizers and pesticides have resulted in a disbalance in nature. Climate change has become a recurring obstacle in agriculture.